Obesity education for nurse practitioners: Perspectives from nurse practitioner faculty. Issue 6 (27th September 2012) - Rogge, Mary Madeline; Merrill, Emily
Abstract Purpose The purpose of the study was to investigate curriculum content and teaching practices about obesity in graduate nursing programs in the United States. Methodology A survey of 1202 faculty members teaching in nurse practitioner (NP) programs was conducted using an investigator‐created instrument with items based on the National Institutes of Health Obesity Education Initiative guidelines. Objective items were analyzed using descriptive and nonparametric statistics, and the open‐ended questions were analyzed using content analysis. Findings NP faculty emphasized existing clinical practice guidelines, but revealed a large disparity between what is emphasized in schools of nursing and the state of the science regarding obesity etiology and management. Faculty place a priority on teaching obesity as a key factor in the development of comorbidities, and weight loss as a means of treating these comorbidities. Teaching about the pathophysiology of obesity, management of bariatric surgery patients, and pharmacologic therapy are de‐emphasized. Four main themes about obesity teaching practices were identified from subjects' comments to open‐ended items. Conclusions Additional education and support are needed for faculty to teach about obesity in a way that advances the care of obese patients based on emerging scientific principles.